Circular code motifs near the ribosome decoding center. (December 2015) - El Soufi, Karim; Michel, Christian J.
Abstract: A maximal C 3 self-complementary trinucleotide circular code X is identified in genes of bacteria, eukaryotes, plasmids and viruses (Michel, 2015; Arquès and Michel, 1996 ). A translation (framing) code based on the circular code was proposed inMichel (2012) with the identification of several X circular code motifs ( X motifs shortly) in both ribosomal RNAs (rRNAs) and their decoding center, and transfer RNAs (tRNAs). We extended these results in two ways. First, three universal X motifs were determined in the ribosome decoding center: the X motif m AA containing the conserved nucleotides A1492 and A1493, the X motif m G containing the conserved nucleotide G530 and the X motif m with unknown biological function (El Soufi and Michel, 2014 ). Secondly, statistical analysis of X motifs of greatest lengths performed on different and large tRNA populations according to taxonomy, tRNA length and tRNA score showed that these X motifs have occurrence probabilities in the 5′ and/or 3′ regions of 16 isoaccepting tRNAs of prokaryotes and eukaryotes greater than the random case (Michel, 2013 ). We continue here the previous works with the identification of X motifs in rRNAs of prokaryotes and eukaryotes near the ribosome decoding center. Seven X motifs PrRNAXm conserved in 16S rRNAs of prokaryotes P and four X motifs ErRNAXm conserved in 18S rRNAs of eukaryotes E are identified near the ribosome decoding center. Furthermore, four very large X motifs of length greater than or equal to 20 nucleotides, 14 large X motifs of length between 16 and 19 nucleotides and several X motifs of length greater or equal to 9 nucleotides are found in tRNAs of prokaryotes. Some properties of these X motifs in tRNAs are described. These new results strengthen the concept of a translation code based on the circular code (Michel, 2012 ).